Prevention and Alleviation of Dextran Sulfate Sodium Salt-Induced Inflammatory Bowel Disease in Mice With Bacillus subtilis-Fermented Milk via Inhibition of the Inflammatory Responses and Regulation of the Intestinal Flora - Zhang, Xuan; Tong, Yanjun; Lyu, Xiaomei; Wang, Jing; Wang, Yuxue; Yang, Ruijin (Frontiers in Microbiology, 2021)
The pathogenesis of inflammatory bowel disease (IBD) might be related to the local inflammatory damage and the dysbacteriosis of intestinal flora. Probiotics can regulate the intestinal flora and ameliorate IBD. The probiotic Bacillus subtilis strain B. subtilis JNFE0126 was used as the starter of fermented milk. However, the therapeutic effects of B. subtilis fermented milk on IBD remains to be explored. In this research, the therapeutic effect of the B. subtilis fermented milk on DSS-induced IBD model mice was evaluated. Besides, the expression pro-inflammatory/anti-inflammatory cytokines, the proliferation of the intestinal stem cells, and the reconstruction of the mucosa barrier were investigated. Finally, the alteration of gut microbiota was investigated by taxonomic analysis. As shown by the results, the DAI of IBD was significantly decreased through oral administration of B. subtilis (JNFE0126) fermented milk, and the intestinal mucosa injury was attenuated. Moreover, B. subtilis could reduce the inflammatory response of the intestinal mucosa, induce proliferation of the intestinal stem cell, and promote reconstruction of the mucosal barrier. Furthermore, B. subtilis could rebalance the intestinal flora, increasing the abundance of Bacillus, Alistipes and Lactobacillus, while decreasing the abundance of Escherichia and Bacteroides. In conclusion, oral administration of the B. subtilis fermented milk could alleviate DSS-induced IBD via inhibition of inflammatory response, promotion of the mucosal barrier reconstruction and regulation of the intestinal flora.